RUSSIAN CLINICAL TRAILS IN CARDIOLOGY. YESTERDAY, TODAY AND TOMORROW - S. A. Shalnova; S. Y. Martsevich (Рациональная фармакотерапия в кардиологии, 2016)
The organization of randomized clinical trials (RCTs) in accordance to the principles of Good Clinical Practice (GCP) is presented. The situation with RCTs in Russia and worldwide is also considered. Issues that must be addressed to improve a quality of the RCTs are reviewed. Information about Russian clinical and epidemiological studies structured for this purpose. The CONSORT (Consolidated Standards of Reporting Trials) Statement was designed to improve the quality of reporting the results of RCTs by group of scientists and editors. Publication of the translation of this important document starts in this issue of the journal.